Validation of the Peruvian Spanish Version of the Stress and Anxiety to Viral Epidemics-6 Scale to Measure Viral Anxiety of Medical Students During COVID-19 - Lapeyre-Rivera, André; Javier-Murillo, Nair; Perea-Flórez, Francisco; Gamonal, Bryan; Velásquez-Rimachi, Víctor; Alva-Díaz, Carlos; Ahmed, Oli; Chung, Seockhoon (Frontiers in Psychiatry, 2022)
Introduction The COVID-19 pandemic has created academic problems for Peruvian medical students leading to anxiety and depression. Hence, validated scales, such as the Stress and Anxiety to Viral Epidemics-6 items (SAVE-6), are required to identify and propose interventions to improve mental health. We aimed to perform a psychometric validation of the Peruvian version of SAVE-6 on medical students during the COVID-19 pandemic in Lima, Peru, in 2022. Methods A total of 260 medical students at National University of San Marcos (UNMSM) participated in an online survey in January 2022. We collected sociodemographic characteristics and classified psychiatric symptoms using SAVE-6, the Generalized Anxiety Disorder-7 items (GAD-7) scale, and the Patient Health Questionnaire-9 items (PHQ-9). We performed confirmatory and parallel factor analysis to examine the validity of the Peruvian Spanish version of SAVE-6. Results We explored the reliability and validity of SAVE-6 and SAVE-6 after excluding item 5, since factor loading of item 5 is too low. Both scales showed good internal consistencies (Cronbach's α = 0.780 and.82 and McDonald's Ω = 0.792 and.829, respectively). Furthermore, SAVE-6 after excluding item 5 showed good convergent validity with GAD-7 (r = 0.224, p <.001) and PHQ-9 (r = 0.217, p <.001). Consequently, instead of the full SAVE-6, SAVE-6 excluding item 5 proved to be reliable and valid enough to assess the anxiety of Peruvian medical students during the pandemic. Conclusion The Peruvian Spanish SAVE-6 scale excluding item 5, rather than the full SAVE-6, can be applied to measure viral anxiety of medical students in Peru with good validity and reliability.